COVID-19: Frequency of positive cases in healthcare professionals at a reference hospital in Paraná (Research, Society and Development, 2021)
The aim of this study was to identify the profile and frequency of infections of the new coronavirus (COVID-19) among healthcare staff at reference hospital for treating the disease. This is a cross-sectional study that used data from COVID-19 Respiratory Syndrome Notification Records and the results obtained by RT-qPCR and Rapid Test. Absolute and relative frequencies were used to describe the sample. For comparisons between positive and negative cases, the chi-square test with Yates continuity correction was deployed, and were considered statistically significant the values that presented p